Statistical databases for economic research on the financing of small firms in the United States - Charles C. Ou (The Journal of Entrepreneurial Finance and Business Ventures, 2005)
This paper updates information about the databases available for researchers in conducting small business financial research. A definition of a statistical database is provided first as a basis for selecting a database suitable for statistical research. Five major databases are discussed in detail, followed by a brief discussion of eight data sources for time series information on activities in specific financing markets for small firms. Comments are provided on the strengths and weaknesses of each of the five major databases regarding their uses for conducting different types of research and on possible areas for improvement.
Keywords: 650